The Feasibility of Investment Installation Using Sea Water Reverse Osmosis (SWRO) In Seribu Island, Indonesia - Dina Maulina; Ave Suakanila Fauzisar (Biological Environment and Pollution, 2021)
Population balance and water availability need to be considered. Indonesia as an agrarian country has abundant marine resource wealth. This condition makes Indonesia a center for marine tourism. The purpose of this research was to analyze water management in Seribu islands as national and foreign marine tourism which are then considered in the provision of sustainable clean water. This research method used descriptive ecological analysis which refers to the literature and data sourced from the amount of groundwater availability based on rainfall, evapotranspiration and dry length. Secondary data collected in this study include statistics and monographs of the study area, climatological meteorological data in the form of rainfall, dry months, and air temperature taken throughout 2019. The results showed that the water quality in the Seribu Islands deteriorated when the dry season arrived and when excessive groundwater extraction occurred. In addition, efforts to develop water management in the Seribu Islands are unplanned and sustainable while the population continues to increase. The growth of homestays, the number of tourists, public facilities such as hospitals, schools, and dormitories triggered the conversion of planting land. Pramuka Island has an unplanned harbor development which has an impact on water resources. Management and planning for the development of Reverse Osmosis Seawater (SWRO) in the Seribu Islands needs to be reconsidered for the supply and management of resources also for the water conservation activities that have not been effective.